If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/2(2x-6)=4(1/4x-3/4)
We simplify the equation to the form, which is simple to understand
1/2(2x-6)=4(1/4x-3/4)
Reorder the terms in parentheses
+(+1x-3)=4*(/4x-0.75)
Remove unnecessary parentheses
+1x-3=+4+*(+/4x-0.75+)
Reorder the terms in parentheses
+1x-3=+(/4x-3)
Remove unnecessary parentheses
+1x-3=+/4x-3
We move all terms containing x to the left and all other terms to the right.
+1x-4x=-3+3
We simplify left and right side of the equation.
-3x=0
We divide both sides of the equation by -3 to get x.
x=-0
| 28y+8=16 | | 6x+29=13-48 | | -7x+8+-4+-9= | | 20*log(x)=55 | | 2.00+1.50=54.5 | | -3(4v-9)+7v=4(v+6) | | 20log(x)=55 | | 2(12p+16)= | | 6=-4.1+r | | x+.06x=400 | | 268+3*g=654 | | -25.8=43v | | 268+3*g=900 | | h=15t-4.9t^2+2 | | c+4.3=-6.7 | | 5x+1=-5x-1 | | (Dy/dx)=3e^5 | | 5.6=f-64 | | 148-(56+j)=24 | | 12x-2.4.2x-1/8x.3x-4 | | 7y+-8y= | | 6.5h=39 | | 4(2x-1)=27+2(2x-5) | | 12x-2.4.2x-1/8x.3x-1 | | 73.2=6.1 | | 6x-34=100x+1 | | 6(2a-b)-15(2a-b)(2a-b)=x | | 3G+2f+9g+4g+4f= | | 4+17=10x+5 | | 6x+23=10x+21 | | 160-(12*j)=78 | | -4+17=10x+5 |